2021
DOI: 10.1016/j.cognition.2020.104552
|View full text |Cite
|
Sign up to set email alerts
|

Sensitive periods for social development: Interactions between predisposed and learned mechanisms

Abstract: We analysed research that makes use of precocial species as animal models to describe the interaction of predisposed mechanisms and environmental factors in early learning, in particular for the development of social cognition. We also highlight the role of sensitive periods in this interaction, focusing on domestic chicks as one of the main animal models for this field. In the first section of the review, we focus on the emergence of early predispositions to attend to social partners. These attentional biases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
40
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 165 publications
(233 reference statements)
2
40
0
Order By: Relevance
“…Preferences for animacy cues, that set apart animate from non-animate objects, have been described in newly hatched chicks, comprising, e.g., preferences for face-like stimuli (Rosa-Salva et al, 2010), biological motion stimuli (Vallortigara et al, 2005;Miura and Matsushima, 2016;Miura et al, 2020) and self-propelled objects that move with variable speed (Rosa-Salva et al, 2016; for review see: Di Giorgio et al, 2017;Lorenzi and Vallortigara, 2021;Vallortigara, 2021). The same animacy cues operate on human newborns and other species, in particular for the preference for speed changes we are dealing with here (see in the human newborns Di Giorgio et al, 2021 and see for reviews: Di Giorgio et al, 2017;Lorenzi and Vallortigara, 2021;Rosa-Salva et al, 2021;Vallortigara, 2021).…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…Preferences for animacy cues, that set apart animate from non-animate objects, have been described in newly hatched chicks, comprising, e.g., preferences for face-like stimuli (Rosa-Salva et al, 2010), biological motion stimuli (Vallortigara et al, 2005;Miura and Matsushima, 2016;Miura et al, 2020) and self-propelled objects that move with variable speed (Rosa-Salva et al, 2016; for review see: Di Giorgio et al, 2017;Lorenzi and Vallortigara, 2021;Vallortigara, 2021). The same animacy cues operate on human newborns and other species, in particular for the preference for speed changes we are dealing with here (see in the human newborns Di Giorgio et al, 2021 and see for reviews: Di Giorgio et al, 2017;Lorenzi and Vallortigara, 2021;Rosa-Salva et al, 2021;Vallortigara, 2021).…”
Section: Introductionmentioning
confidence: 93%
“…Although imprinting can occur with either naturalistic stimuli (resembling a conspecific) or artificial objects, a large amount of evidence shows the existence of spontaneous unlearned preferences for animate features (Rosa-Salva et al, 2021). These preferences act as a sort of canalisation mechanism to direct the newborns' attention, favouring exposure to stimuli that are more likely to be social partners (Di Giorgio et al, 2017;Versace et al, 2018;Rosa-Salva et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, it is crucial to consider that many of the species in which a preference for biologically moving stimuli has been observed are highly social. Indeed, it has been amply argued that an innate “agent detection” system may exist because of the need of these animals to quickly aggregate with social companions (Rosa-Salva et al, 2021). In such species it would be advantageous to show an early attentional preference to movements which are more likely to be generated from an agent.…”
Section: Discussionmentioning
confidence: 99%
“…As a learning mechanism, imprinting is notable because it lacks a specific form of explicit (observable) reinforcement (2) thus exposing both nature and nurture in one sweep, where the mechanism in itself is inherited and narrowly pre-specified, but the content of what is learned is to a large degree left to reflect the circumstances of the newborn. Recent research has shown that, i) sensory pre-dispositions are crucial, facilitating neonates' orientation towards relevant features of the environment (3,4), while ii) abstract, and logical, relational concepts can be acquired by newly hatched ducklings through imprinting (5). This latter discovery suggests that information learnt during filial imprinting resembles more closely multidimensional vectors that represent potentially abstract concepts than libraries of direct percepts.…”
Section: Introductionmentioning
confidence: 99%